Investigating Learners' Perceptions of Microlearning: Factors Influencing Learning Outcomes - Monib, Wali Khan; Qazi, Atika; Apong, Rosyzie Anna; Mahmud, Malissa Maria (IEEE access, 2024)
Microlearning, characterized by its concise and targeted learning content, has emerged as a dynamic pedagogical approach. However, its effect on learning outcomes is subject to mixed research findings, and there is limited understanding of the underlying factors influencing these outcomes. To address this gap, we collected both quantitative and qualitative data from life-long learners who were taking micro modules. This study identified and categorized specific content level factors and learner level factors into contextual (media richness), behavioral (interaction and engagement), cognitive (comprehension), and affective (motivation, self-concept, and satisfaction), influencing learning outcomes drawing from multiple theories such as the Expectancy-Disconfirmation, constructivism, Self-determination, Situational Awareness, Cognitive Multimedia Learning, and Andragogy. The study introduced a novel framework to investigate factors influencing learning outcomes. We utilized SmartPLS for quantitative analysis and ATLAS.ti for qualitative analysis. Quantitative findings revealed significant influence of media richness on interactivity, engagement, satisfaction, and comprehension. Interactivity significantly influenced engagement, and engagement, in turn, shaped learner satisfaction and self-concept. Additionally, comprehension significantly influenced both satisfaction and learning outcomes. However, interactivity, engagement, and satisfaction did not significantly affect learning outcomes. Qualitative analysis identified specific challenges like limited peer interaction, pace of instruction, and comprehension difficulties with complex content. However, it also highlighted positive aspects such as flexibility and accessibility. This research provides valuable implications for curriculum designers, policymakers, educational tools developers, and educators to develop effective microlearning content.